2022
DOI: 10.1101/2022.02.13.480261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Omicron Spike protein has a positive electrostatic surface that promotes ACE2 recognition and antibody escape

Abstract: High transmissibility is a hallmark of the Omicron variant of SARS-CoV-2. Understanding the molecular determinants of Omicron transmissibility will impact development of intervention strategies. Here we map the electrostatic potential surface of the Spike protein to show that major SARS-CoV-2 variants have accumulated positive charges in solvent-exposed regions of the Spike protein, especially its ACE2-binding interface. Significantly, the Omicron Spike-ACE2 complex has complementary electrostatic surfaces. In… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Thus, the effort of the scientific community has been mainly focused on the description of the most immunogenic regions of the Spike protein, and how the variant's amino acid substitutions can impact the binding with known antibodies. [52][53][54][55] A complete overview of the various antibody-spike complexes experimentally determined has been furnished in this recent paper, with particular attention to the epitope region the antibodies are bound to. 56 However, we focused on a different aspect.…”
Section: Sequence and Structural Analysis Of Anti-spike Antibodiesmentioning
confidence: 99%
“…Thus, the effort of the scientific community has been mainly focused on the description of the most immunogenic regions of the Spike protein, and how the variant's amino acid substitutions can impact the binding with known antibodies. [52][53][54][55] A complete overview of the various antibody-spike complexes experimentally determined has been furnished in this recent paper, with particular attention to the epitope region the antibodies are bound to. 56 However, we focused on a different aspect.…”
Section: Sequence and Structural Analysis Of Anti-spike Antibodiesmentioning
confidence: 99%
“…Kumar et al ( 30 ) showed that Omicron and its subvariants have a higher affinity for human angiotensin-converting enzyme 2 (ACE2) compared with the wild type and Delta variants because of a significant number of mutations in the RBD, therefore, a potentially higher transmission rate ( 30 ). Computational analysis perform by Gan et al ( 31 ) showed that Omicron Spike trimer surface has transitioned to strongly positive electrostatic surface compared to Wuhan-Hu-1 variant. This result suggest that Omicron mutations not only enhance ACE2 recognition but also cause antibody escape ( 31 ).…”
Section: Omicron Genomicsmentioning
confidence: 99%
“…Computational analysis perform by Gan et al ( 31 ) showed that Omicron Spike trimer surface has transitioned to strongly positive electrostatic surface compared to Wuhan-Hu-1 variant. This result suggest that Omicron mutations not only enhance ACE2 recognition but also cause antibody escape ( 31 ). BA.2 and BA.3 have a higher transmission potential compared with the BA.1 and BA.1.1 ( 26 ).…”
Section: Omicron Genomicsmentioning
confidence: 99%